2008
DOI: 10.1007/s11255-007-9322-7
|View full text |Cite
|
Sign up to set email alerts
|

Successful steroid treatment in a patient with membranoproliferative glomerulonephritis associated with hepatitis C virus

Abstract: Thirteen years ago, a 65-year-old woman was diagnosed to have chronic active hepatitis with hepatitis C virus. After starting interferon alpha administration, she noticed edema and hypoalbuminemia. Renal biopsy revealed mesangial proliferation with focal endocapillary proliferation, and double contour of the glomerular basement membrane due to mesangial interposition. Interferon alpha was discontinued, and proteinuria and edema gradually decreased. She was re-admitted due to a relapse of proteinuria 8 years la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Like IFN therapy, steroid therapy is also controversial; however, to our knowledge, no cases of steroid therapy exacerbating cryoglobulinemia have been reported. In many case reports, steroids were the drugs of first choice 39 . Steroids have been expected, on a theoretical basis, to inhibit virus-induced autoimmunity; however, because of the possibility of viral replication due to steroid therapy, patients should be closely observed.…”
Section: Discussionmentioning
confidence: 99%
“…Like IFN therapy, steroid therapy is also controversial; however, to our knowledge, no cases of steroid therapy exacerbating cryoglobulinemia have been reported. In many case reports, steroids were the drugs of first choice 39 . Steroids have been expected, on a theoretical basis, to inhibit virus-induced autoimmunity; however, because of the possibility of viral replication due to steroid therapy, patients should be closely observed.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroid therapy for HCV-related glomerulonephritis was recommended together with IFN therapy in the KDIGO guidelines [10], and there are several reports of corticosteroid therapy for HCV-related glomerulonephritis [13,14]. In a randomized controlled study, Dammacco et al [15] reported the use of corticosteroid therapy for type II mixed cryoglobulinemia.…”
Section: Discussionmentioning
confidence: 99%
“…ПТ ГК активно применяют для лечения таких заболеваний, как системная красная волчанка (СКВ) [13, 16,21], гломерулонефриты [19,39], РА и системные васкулиты (СВ) [28,45]. В исследование С. Tani (2010) были включе-Казанский медицинский журнал, 2013 г., том 94, №6 ны 30 женщин с СКВ и диффузным пролиферативным гломерулонефритом, получавших ПТ ГК и краткий курс ПТ циклофосфамидом.…”
unclassified